Effectiveness Of Red Ginger Herbal Beverage As A Biomarker-Based Occupational Health Intervention On Blood Lactic Acid Levels Among Trans Metro Pekanbaru Bus Drivers With Low Back Pain - Yuharika Pratiwi; Bintang Ramadhani (CV. AFDIFAL MAJU BERKAH, 2026)
Low back pain (LBP) is one of the most common musculoskeletal disorders among transportation workers, particularly bus drivers. Prolonged sitting posture, non-ergonomic working conditions, and continuous exposure to whole-body vibration contribute to impaired muscle perfusion and increased anaerobic metabolism, resulting in elevated blood lactate levels. Red ginger (Zingiber officinale var. rubrum) contains bioactive compounds such as gingerol and shogaol, which possess anti-inflammatory, antioxidant, and vasodilatory properties that may facilitate lactate clearance and reduce muscle pain. To evaluate the effectiveness of red ginger beverage on blood lactate levels among bus drivers with low back pain. This study used a quasi-experimental design with a pretest-posttest control group approach. A total of 60 Trans Metro Pekanbaru bus drivers with LBP were divided into an intervention group (n=30) and a control group (n=30). The intervention group received a red ginger beverage containing 10 g of red ginger in 100 mL of solution, while the control group received a beverage without the active components of red ginger. Blood lactate levels were measured before and after the intervention using the Accutrend® Plus device. Data normality was assessed using the Shapiro–Wilk test. Within-group differences were analyzed using the Wilcoxon signed-rank test, while between-group differences were analyzed using the independent t-test and Mann–Whitney test. Before the intervention, mean blood lactate levels were relatively comparable between the intervention group and the control group, with values of 3.01±0.65 mmol/L and 2.98±0.66 mmol/L, respectively. There was no significant difference in baseline blood lactate levels between the two groups (p=0.841 by Mann–Whitney test). After the intervention, blood lactate levels decreased in both groups. The intervention group showed a greater reduction, from 3.01±0.65 mmol/L to 1.99±0.31 mmol/L, with a mean decrease of 1.02±0.45 mmol/L. In the control group, blood lactate levels decreased from 2.98±0.66 mmol/L to 2.59±0.58 mmol/L, with a mean decrease of 0.39±0.22 mmol/L. The Mann–Whitney test showed a significant difference in post-intervention blood lactate levels between the intervention and control groups (p<0.001), with lower lactate levels observed in the intervention group. The administration of red ginger beverage had an effect on reducing blood lactate levels among TMP bus drivers with low back pain. The reduction in blood lactate levels was greater in the intervention group than in the control group, suggesting that red ginger beverage has the potential to be used as a supportive non-pharmacological intervention to reduce muscle pain among bus drivers with low back pain.